Pengaruh Intensitas R&D dan Profitabilitas terhadap Corporate Social Responsibility pada Perusahaan Sektor Manufaktur - Sari, Warsani Purnama; Utari, Eva Tri; Prayudi, Ahmad (Mahesa Research Center, 2025)
This research aims to analyze the influence of RD intensity and profitability on Corporate Social Responsibility (CSR) in Manufacturing Sector RD companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The samples in this research are several manufacturing sector companies listed on the BEI in 2017-2023 according to predetermined criteria, namely INTP, SMGR, TOTO, ISSP, JPFA, MAIN, SPMA, ASII, CAMP, ICBP, INDF, MLBI, GGRM, WIIM, KAEF, SIDO, INVR and CINT. The independent variables in this research are RD intensity and profitability, while the dependent variable is CSR. Data analysis was carried out using multiple linear regression tests. The research results show that RD intensity has a positive and significant effect on the CSR of manufacturing sector companies listed on the Indonesia Stock Exchange. Profitability has a positive and significant effect on the CSR of manufacturing sector companies listed on the Indonesia Stock Exchange. RD intensity and profitability simultaneously have a significant effect on the CSR of manufacturing sector companies listed on the Indonesia Stock Exchange. The influence (determination) of R D intensity and overall profitability on CSR is 21.50%. This shows that CSR is also influenced by other factors outside the variables of CSR intensity and profitability, where this influence is relatively large, namely 78.5%.